First molar extraction an option in Orthodontics: A report of two cases - Mahajan, Monika (Journal of Orofacial Research, 2020)
Orthodontic treatment requires extraction of teeth in several cases. Permanent first molar becomes a viable option in cases where they are in compromised condition due to extensive caries, hypoplasia, periapical pathology and periodontal diseases. Proper selection of case with appropriate biomechanics makes it possible to achieve good results not only in occlusion but also in soft tissue changes resulting in short duration of treatment and good clinical outcome. However, for the success of the treatment it is necessary to take into consideration different intramaxillary and intermaxillary factors along with consideration for balancing and or compensating extraction. Here we present two cases where with the extraction of compromised permanent first molars, we were able to establish a stable functional occlusion with an improved profile and a pleasant smile.